Telecommunication companies’ tales to strengthen brand: analysis of television spots during pandemic confinement - Dettleff Pallete, James Anthony (2022)
The mandatory lockdown in Peru wich lasted over three months made the telecommunication companies redefine their strategies to fase pandemic. This Project analyzes the TV spots of the three main telecommunication companies in Peru in order to identify their narratives, the way the faced the pandemic, the audiovisual resources thay had to use, and the way they turned to social advertising to strengrhen their brands. We worked with an analysis matrix and semi-structured interviews with marketing managers to constrast our main findings. The priority for these companies was to answer to the emergency by guaranteeing connectio, wich was in line with their Brand purpose, based mainly in emotional speeches and positioning themselves as solutions for their clients during the pandemic scenario. We conclude that the narratives were used as social advertising tolos to strengthen brand equity, but mainly targeting their own clients.